Resurgence of pertussis and strategies of B. pertussis to evade acellular vaccine induced immunity - Niinikoski, Vili (My University, 2024)
In countries where acellular pertussis (aP) vaccines are used, there has been a rise in B. pertussis isolates that do not produce certain vaccine antigens, such as pertactin (PRN). In Finland, the whole-cell pertussis (wP) vaccine was replaced by aP vaccines in 2005, which contained only two components: pertussis toxin (PT) and filamentous hemagglutinin (FHA). In 2009, the aP vaccines were changed to a three-component vaccine, which included PT, FHA, and PRN. Two years after the change, first PRN-deficient isolate was reported. After that number of PRN-deficient isolates has increased, but no PT or FHA-deficient isolates were found. Whether B. pertussis has used different strategy for other aP vaccine antigens remains to be discovered. The objective of our study was to examine changes in the expression of four antigens, including three (PT, PRN, and FHA) that are present in aP vaccines, and one (adenylate cyclase toxin or ACT) that is not included in current aP vaccines. We analyzed Finnish isolates collected over the past 30 years. We included three hundred isolates, chosen at random from the Finnish Reference Laboratory for Pertussis and Diphtheria located in Turku, Finland, between 1991 and 2020. We employed an adjusted ELISA-based assay that uses monoclonal antibodies and included culturing B. pertussis in Stainer-Scholte medium to assess antigen expression levels. The expression of each antigen by individual isolates was compared using arbitrary units. Following the implementation of aP vaccines, there has been a substantial rise in the number of PRN deficient isolates, and even PRN positive isolates have shown a decrease in PRN expression, particularly after the use of aP vaccines containing PRN. However, we did not detect any FHA or ACT negative isolates, and the production of PT, FHA, and ACT in the B. pertussis strains isolated after 2010 has significantly increased. Nevertheless, only the increase in FHA and ACT expression was correlated with the introduction of aP vaccines. The study revealed that B. pertussis has employed distinct strategies for the production of different antigens in response to selection pressure induced by aP vaccines. After the introduction of aP vaccines in Finland, the production of FHA and ACT increased significantly in B. pertussis isolates. These findings highlight the need for further investigation into the production of FHA and ACT in B. pertussis strains from countries with varying aP vaccines and immunization programs.
Keywords: Pertussis, B. pertussis, Resurgence